Memahami Kehadiran Nyata Kristus dalam Ekaristi Menurut Dokumen Mysterium Fidei - Martha Ade Citra Muliana Halawa; Alexius Poto Obe; Bartolomeus Sihite (Journal New Light, 2024)
The Eucharist is the most beutifull gift that Jesus Christ himself gave us have us his people as a manisfestation of His love for us.The Catholic Churh teaches that Christ is truly present in the Eucharist and makes Himself the food and drink of believers. However, many Catholics do not understand the presence of Christ in the Eucharist and even attend the Eucharist celebration haphazardly.Such as afterreceiving communion, immediately cursing, telling stories in Church, playing with cell phones during Eucharist celebrations, taking photos in front of the Tabernacle without respecting and distinguishing the meaning of private mass from community mass.Dotted starting from concerns about the lack of understanding of the Presence of Christ in the Eucharist, the author chose this theme so that people can better appreciate and understand the Presence of Christ in the Eucharist according to the Mysterium Fidei dokumen. To deepen this theme, the author uses a literature review method. From library sources, the author summarizes that through Tansubstantiation the bread and wine are truly the body and blood of Christ which He offered for the salvation of mankind.For this reason, we as Catholic believers welcome the Body and Blood of Christ in the celebration and make room for Him in our hearts. So that we feel salvation from Him because His presence in the Eucharist cannot and intelligence but only with faith.